ABNORMAL RETURNS IN THE BRAZILIAN FINANCIAL SYSTEM: DOES CONTROL MATTER? - Costa, Renata Sol; Antunes, José Américo; Macedo, Marcelo Alvaro; Sarlo Neto, Alfredo (Advances in Scientific and Applied Accounting, 2017)
The purpose of this paper is to investigate the influence of the control structure in abnormal returns in the Brazilian Financial System, contributing to the scarce literature available. The relevance of this study remains on the fact that the Brazilian Financial System differs significantly from developed or even other emerging economies’ financial systems due to the relevance of the market share detained by state-owned banks. This feature influences the behavior of the financial system and makes Brazil an interesting case study. The analysis segments the Brazilian Financial System into three groups: all banks, state-owned banks and private banks, and evaluates the influence of relevant income and expense components such as credit spread, credit provisions and service income in the abnormal returns of each segment through aggregate data analysis. Our findings suggest that the behavior of the financial system depends on the control structure when considering the spread charged in credit operations as well as the credit provisions, presenting different realities when considering its segments. On the other hand, the control structure does not seem to be relevant for service income.